RESERVOIR CONNECTIVITY STUDY OF G057B & G058B ZONES IN NILAM FIELD, KUTEI BASIN, EAST KALIMANTAN - HARSIAN, HENDRI
n et al. (2007) proposed the static and dynamic approach in studying reservoir connectivity. These approaches tried to be applied in the reservoir connectivity study of G057B and G058B sand in Nilam Field, Kutei Basin, East Kalimantan, Indonesia. Nilam Field is part of Sanga Sanga PSC where VICO Indonesia operates and already reached mature stage as a gas field. Production started from 1974 and today more than 250 wells have been drilled and to date the production already reach 3.5 TCF gas. Reservoir model have been develop since exploration stage, but as new data gathered this model have to be updated and revised. Reservoir connectivity study of G057B and G058B started by remapping and building its geological model. Sequence stratigraphy approach applied in remapping the stratigraphy of both sands. G057B and G058B are channel fill and bars deposits in upper deltaic depositional environment. Both facies interpretation base on open hole log data, except G057B facies interpretation supported by core analysis from NLM0600. Seismic 3D, gas chromatography analysis result and permeability data from ELAN Volume analysis were integrated to geological model. Unfortunately, due to lack of data quantity and quality, the optimum result couldn’t be reach for reservoir connectivity of G057B and G058B sands from the integration. Pressure data from RFT/MDT and production data analysis then used in integration with geological model and help in refining reservoir connectivity definition of G057B and G058B sands. As the result 11 reservoirs (tanks) defined for G057B and 14 reservoirs (tanks) defined for G058B. Reservoir distribution of both sands plotted in reservoir connectivity maps. The geological model of reservoirs derived from net sand distributionis not consistent with reservoir connectivity distribution based on integrated study result. This probably due to diagenetic control in NIlam Field which taken place after the deposition, as shown by calcareous nodules and well-cemented sandstones. At the end, found that dominant contribution for reservoir connectivity distribution of G057B and G058B sand in Nilam Field were geological model and pressure trend analysis result. Then its recommended to do further study if other data supporting the reservoir connectivity are available.